Peningkatan Kualitas Air Mata Untuk Mendukung Sekolah Adiwiyata di SMPN 1 Cangkringan - Yandhia Febrina Putri; Rahmad Setya Adilasana; Della Anggreani; Miftasyafani Winda Puspita Dewi; Dwi Ariyati; Tania Edna Bhakty (STMIK Royal, 2026)
Abstract: Clean water availability plays an important role in supporting sanitation, environmental health, and educational activities in schools. SMP Negeri 1 Cangkringan has a natural spring water source containing iron (Fe) levels of 1–2 mg/L, exceeding the water quality standard stipulated in Indonesian Ministry of Health Regulation No. 32 of 2017. This community service program aimed to improve water quality through the implementation of a simple treatment system based on aeration, sedimentation, and filtration, while also supporting the Adiwiyata School Program. The implementation method applied a participatory approach involving teachers, students, and educational staff through several stages, including identification of water quality problems, initial water quality testing, design of aeration and filtration systems, installation of the water treatment unit, post-treatment water quality testing, as well as monitoring and evaluation of program sustainability. The filtration system utilized gravel, silica sand, activated carbon, and zeolite stone as filter media. Water quality testing was conducted before and after treatment to evaluate the effectiveness of Fe reduction. The results showed that the aeration and filtration system successfully reduced Fe concentrations from 1–2 mg/L to 0.5–1 mg/L with an efficiency of 50–75%, thereby meeting the hygiene and sanitation water quality standards. In addition, the program enhanced environmental awareness among school members through practice-based learning activities. Keywords: aeration; community service; filtration; iron (Fe); spring water quality; sustainability education. Abstrak: Ketersediaan air bersih memiliki peran penting dalam mendukung sanitasi, kesehatan lingkungan, dan aktivitas pendidikan di sekolah. SMP Negeri 1 Cangkringan, Yogyakarta memiliki sumber mata air alami dengan kandungan zat besi (Fe) sebesar 1–2 mg/L yang melebihi baku mutu berdasarkan Permenkes RI No. 32 Tahun 2017. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kualitas air melalui penerapan sistem pengolahan sederhana berbasis aerasi, sedimentasi, dan filtrasi sekaligus mendukung program Sekolah Adiwiyata. Metode pelaksanaan menggunakan pendekatan partisipatif dengan melibatkan guru, siswa, dan tenaga kependidikan melalui tahapan identifikasi permasalahan kualitas air, pengujian awal kualitas air, perancangan sistem aerasi dan filtrasi, implementasi instalasi pengolahan air, pengujian kualitas air pasca pengolahan, serta monitoring dan evaluasi keberlanjutan program. Sistem filtrasi menggunakan media kerikil, pasir silika, arang aktif, dan batu zeolit. Pengujian kualitas air dilakukan sebelum dan sesudah pengolahan untuk mengetahui efektivitas penurunan kadar Fe. Hasil kegiatan menunjukkan bahwa sistem aerasi dan filtrasi mampu menurunkan kadar Fe dari 1–2 mg/L menjadi 0,5–1 mg/L dengan efisiensi sebesar 50–75%, sehingga memenuhi baku mutu air higiene sanitasi. Program ini juga meningkatkan kesadaran lingkungan warga sekolah melalui pembelajaran berbasis praktik. Kata kunci: aerasi; filtrasi; pengabdian kepada masyarakat; peningkatan kualitas air; Sekolah Adiwiyata; zat besi (Fe).